Desain Sistem Pengurasan Dan Pengisian Air Kolam Pembenihan Ikan Secara Otomatis Menggunakan Arduino Dengan Sensor Kekeruhan Air - Nelly Khairani Daulay (Jurnal Khatulistiwa Informatika, 2018)
The system of filling and draining of fishpond pond water in the area of UPB (Certified Seedling Unit) Pedasaan J. Ngadirejo District Tugumulyo still manual by using human power. Pool in the drain while cleaned periodically, then just fill with fresh water. To shorten the time of draining and minimize human power in the cleaning process then make a system of draining and water filling automatically by using water turbidity sensor. In this design, two pumps are used, one pump is in a seeding tub and two pumps are in a water reservoir. The working system of this design is as follows: as a pool dewatering controller and automatic charging by the arduino uno microcontroller and the water level is measured with the water level sensor. The dewatering process is carried out when the water turbidity sensor has detected that the pond water has reached the maximum limit of turbidity and water should be replaced immediately. The turbidity sensor of the water will send an order to the arduino to control the pump one so that pump one will open and drain the water from the hatchery pool then the draining and cleaning process can begin. After the pool is clean, and the water level sensor reads that the water in the pool has reached the minimum limit of the sensor then, the sensor will immediately transmit the signal to the arduino uno microcontroller to close the solenoid at the pump one in the bath tub and open the solenoid at the pump two in the water reservoir so can clean water to the hatchery pond. As for to enable electronics circuits on the system that is made then in need of supply voltage from the power supply of + 5V. This power supply circuit consists of a 12Volt output transformer, current rectifier with Brige Diode, filter (Elcho) and LM 7805 regulator IC.